The effectiveness of the Incredible Years pre-school parenting programme in the United Kingdom: a pragmatic randomised controlled trial. Issue 2 (3rd April 2017) - Morpeth, Louise; Blower, Sarah; Tobin, Kate; Taylor, Rod S.; Bywater, Tracey; Edwards, Rhiannon Tudor; Axford, Nick; Lehtonen, Minna; Jones, Carys; Berry, Vashti
ABSTRACT: The prognosis for children with early-onset conduct disorder is poor. Conduct disorder also has a social cost for families and communities, and an economic cost for society through the increased use of health, education, social, legal and detention services. In this study, the Incredible Years (IY) BASIC programme was delivered to parents of pre-school children at risk of developing a conduct disorder and evaluated by pragmatic randomised controlled trial. Participants were parents of 161 children (110 intervention, 51 control) aged between 36 and 59 months (mean age 44 months, 63% boys) and scoring over the clinical cut-off on the Strengths and Difficulties Questionnaire (SDQ). At follow-up (six months post-baseline), the intent-to-treat analysis showed a mean between group difference in favour of IY on the SDQ total difficulties score of 2.23 ( p < 0.05, effect size: 0.50). IY was also superior to control on the Eyberg Child Behaviour Inventory ( p < 0.05, effect size: 0.37) and on the Arnold and O'Leary parenting scale ( p < 0.01, effect size: 0.43). This study confirms the effectiveness of IY in a public system delivered with fidelity by regular children's centre staff, supporting findings from a similar trial in Wales. These results support the wider roll-out of IY to similar children.